Glass cloth, prepreg and printed wiring board

By adjusting the Fe content and appropriate Si, B and F content in the glass line, the problem of the existing low-dielectric constant glass cloth reducing strength after heat treatment is solved, and the balance between low-dielectric constant and high-strength is achieved, and it is suitable for the preparation of pre-prepared materials and printed circuit boards with high stability.

JP2025060927AInactive Publication Date: 2025-04-10ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024231539
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the existing low-dielectric constant glass cloth increases the dielectric constant, it is easy to cause the elastic modulus of the glass line to decrease. After heat treatment, the strength of the glass cloth is significantly reduced, it is easy to break, and it is easy to cause fracture problems when preparing the pre-prepared materials.

Method used

By adjusting the Fe content in the glass line, it maintains a certain intensity after heat treatment, and suppresses the change in dielectric constant. The Fe content is controlled between 0.001% and 0.05%, combined with the appropriate Si, B and F content, the low dielectric constant and high strength of the glass cloth are ensured.

Benefits of technology

It is achieved while maintaining a low dielectric constant, suppressing the decrease in the strength of the glass cloth, improving the break resistance and stability of the glass cloth, and is suitable for preparing pre-prepared materials and printed circuit boards with low dielectric constant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060927000001
    Figure 2025060927000001
  • Figure 2025060927000002
    Figure 2025060927000002
Patent Text Reader

Abstract

To provide a low dielectric glass cloth with both of variation in dielectric properties and strength degradation suppressed, and a prepreg and a printed wiring board made of the low dielectric glass cloth.SOLUTION: A glass cloth including a glass yarn made of a plurality of glass filaments as warp and weft has a weight loss factor obtained as a product of a weight loss ratio derived from the glass component in heat treatment at 380°C for 2 hours and an average radius of the glass filament in the following equation (1) of more than 0.45 and 0.90 or less. The glass cloth has an Fe content in terms of Fe2O3 of 0.001 mass% or more and 0.05 mass% or less. Weight loss factor=The weight loss ratio (%)×Average radius of the glass filament (μm) ... (1)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass cloth, a prepreg, and a printed wiring board. [Background technology]

[0002] With the recent development of the information and communication society, data communication and / or signal processing have become large-volume and high-speed, and the dielectric constant of printed wiring boards used in electronic devices has been significantly reduced. For this reason, many low-dielectric glass cloths have been proposed as glass cloths for use in printed wiring boards.

[0003] For example, the low dielectric glass cloth disclosed in Patent Document 1 achieves a low dielectric constant by incorporating a large amount of B2O3 into the glass composition, as compared to the E-glass cloth that has been commonly used conventionally, while at the same time adjusting the amounts of other components such as SiO2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-292567 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the B2O3 content in the glass yarn is increased to lower the dielectric constant of the glass cloth, the elastic modulus of the glass yarn is decreased and the strength of the glass cloth after heat treatment is significantly decreased. Therefore, there is a problem that the glass cloth is easily broken. When such a glass cloth is used to manufacture a prepreg, the glass cloth breaks in situations where an external load is applied to the glass cloth, such as an operation to control the amount of resin attached, causing a production problem.

[0006] Regarding this point, Patent Document 1 discloses a method of suppressing the volatilization of B2O3 by setting the B2O3 content to less than 20 mass% and the CaO content to a specified range during spinning of glass yarn. However, setting the B2O3 content to less than 20 mass% does not fully meet the demand for low dielectric constant, and ultimately, a glass cloth with low dielectric constant and suppressed strength reduction has not been realized. Furthermore, it has been found that when the weight loss during heat treatment is within a specific range, the strength reduction becomes more serious.

[0007] Furthermore, it has been found that when attempting to suppress volatilization by adding other components, as in the method described in Patent Document 1, there is a possibility that variations in dielectric properties may occur in the surface direction of the glass cloth or between lots.

[0008] The present invention has been made in consideration of the above problems, and has an object to provide a low dielectric glass cloth in which both the variation in dielectric properties and the decrease in strength are suppressed, and a prepreg and a printed wiring board using the low dielectric glass cloth. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems and found that, by adjusting the Fe content in a glass yarn having a predetermined weight loss tendency, a glass cloth obtained by using the glass yarn can solve the above problems, thereby completing the present invention.

[0010] That is, the present invention is as follows. [1] A glass cloth constructed by using glass yarns made of a plurality of glass filaments as warp yarns and weft yarns, In the following formula (1), a weight loss coefficient calculated as the product of the weight loss rate derived from the glass component in a heat treatment at 380° C. for 2 hours and the average radius of the glass filaments is more than 0.45 and 0.90 or less, Weight reduction coefficient=weight reduction ratio (%)×average radius of the glass filaments (μm) (1) The Fe content of the glass cloth is 0.001% by mass or more and 0.05% by mass or less in terms of Fe2O3. Glass cloth. [2] The glass cloth, The F content is 0.001 to 0.1 mass%. The glass cloth according to [1]. [3] The glass cloth, The Si content is 40 to 60 mass% in terms of SiO2, The B content is 15 to 30 mass% calculated as B2O3. The glass cloth according to [1] or [2]. [4] The elastic modulus of the glass cloth is 50 to 70 GPa. The glass cloth according to any one of [1] to [3]. [5] The elastic modulus of the glass cloth is 50 to 63 GPa. The glass cloth according to [4]. [6] The average diameter of the glass filaments constituting the warp and weft yarns is independently 3.5 to 5.4 μm. The glass cloth according to any one of [1] to [5]. [7] Has a dielectric constant of 5.0 or less at a frequency of 1 GHz; The glass cloth according to any one of [1] to [6]. [8] [1] to [7], and and a matrix resin impregnated in the glass cloth. Prepreg. [9] The glass cloth according to any one of [1] to [7] is provided. Printed wiring board. Effect of the Invention

[0011] According to the present invention, it is possible to provide a low dielectric glass cloth in which both the variation in dielectric properties and the decrease in strength are suppressed, and a prepreg and a printed wiring board using the low dielectric glass cloth. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Below, we will explain in detail the embodiment of the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0013] [Glass cloth] The glass cloth of the present embodiment is a glass cloth constituted of glass yarns each consisting of a plurality of glass filaments as warp and weft yarns, in which a weight reduction coefficient calculated as the product of the weight reduction rate derived from the glass component in a heat treatment at 380°C for two hours and the radius of the glass filaments in the following formula (1) is more than 0.45 and 0.90 or less, and the Fe content of the glass cloth is 0.001% by mass or more and 0.05% by mass or less, calculated as Fe2O3. Weight reduction coefficient=weight reduction ratio (%)×average radius of the glass filaments (μm) (1)

[0014] In the case of glass cloth having a low dielectric constant, the strength of the glass cloth is gradually reduced during heat treatment in the manufacturing process or in a subsequent heat treatment. This reduction in strength and the low elastic modulus of the glass yarn constituting the low dielectric glass cloth make the low dielectric glass cloth more susceptible to breakage than those using other glass yarns such as E glass. In this embodiment, the strength reduction due to heat treatment is suppressed by adjusting the Fe (iron) content in the glass, and more preferably the F (fluorine) content, in the glass loss having a predetermined weight reduction tendency.

[0015] The reason why the strength reduction can be suppressed by adjusting the Fe content is not limited, but is considered to be as follows. During spinning, even if sparse parts occur in the glass yarn, the molten glass can flow to fill the parts, and this flow can eliminate the parts where the glass yarn becomes sparse and brittle due to weight loss. On the other hand, even if sparse parts occur in the glass yarns constituting the glass cloth, the glass cannot flow to fill the parts. Under these circumstances, in the glass cloth of this embodiment, it is considered that Fe incorporated in the glass structure may act to hold together the parts where the glass yarn becomes sparse and brittle due to weight loss.

[0016] In addition, the reason why the variation in the dielectric properties can be suppressed by adjusting the Fe content is not limited, but is considered to be as follows. The glass yarn is basically composed of amorphous parts, but the part where Fe exists can be considered to be a part with relatively high crystallinity. In this way, when a part of the composition constituting the amorphous part volatilizes from the glass yarn in which a part with high crystallinity exists locally in the amorphous, it is considered that the variation in the dielectric properties occurs depending on the way the highly crystalline part exists. In particular, when the Fe content is excessive, it is considered that the variation in the dielectric properties caused in this way becomes more apparent, but in this embodiment, the variation in the dielectric properties can be suppressed by adjusting the Fe content. In particular, the lower the dielectric constant and the dielectric tangent, the greater the effect of suppressing the variation in the dielectric properties by adjusting the Fe content tends to be.

[0017] In addition, the reason why the strength reduction is further suppressed by adjusting the F content is not limited, but is considered to be as follows. F reduces the viscosity of molten glass in the glass manufacturing process. Therefore, when the F content is within a predetermined range, metal components such as Fe are uniformly dispersed without localization when they are incorporated into the glass structure, and uniform glass can be formed. It is considered that the effect of Fe connecting the parts where the glass threads become sparse due to the volatilization of the above-mentioned glass components is more effectively expressed by Fe being uniformly dispersed. In addition, it is considered that if hard parts are unevenly distributed in the glass due to the localization of Fe, etc., it is likely that breakage will occur starting from those parts, but it is considered that such localization can be alleviated by adjusting the F content, and the strength reduction can be further suppressed.

[0018] Furthermore, the reason why the variation in dielectric properties is further suppressed by adjusting the F content is thought to be as follows, although it is not limited thereto: F reduces the viscosity of molten glass in the glass manufacturing process as described above, so that by keeping the F content within a specified range in addition to adjusting the Fe content, the local occurrence of relatively highly crystalline areas where Fe is present is significantly suppressed, and a more uniform glass is formed, thereby suppressing the variation in dielectric properties.

[0019] By having the above-mentioned configuration, the present embodiment can solve the breakage problem that the low dielectric glass cloth has, and can provide a glass cloth having high breakage resistance and low and less variable dielectric properties. The configuration of the present embodiment will be described in more detail below.

[0020] (Weight reduction coefficient) The weight loss coefficient (hereinafter, also simply referred to as "weight loss coefficient") calculated as the product of the weight loss rate derived from the glass component and the average radius of the glass filaments when the glass cloth is heat-treated at 380°C for 2 hours is more than 0.45 and 0.90 or less, preferably 0.47 or more and 0.85 or less, and more preferably 0.48 or more and 0.80 or less.

[0021] "Weight loss ratio derived from glass components" means that the weight loss ratio in the case of heat treatment at 380°C for 2 hours is due to the disappearance of glass components due to volatilization during heat treatment. As described later, in the present embodiment, when a surface treatment agent such as a silane coupling agent is attached to the glass cloth or when a large amount of organic impurities is attached, the weight loss ratio is calculated after removing the surface treatment agent such as a silane coupling agent or the organic impurity attached components that are physically adsorbed with a good solvent such as alcohol or acetone. Therefore, the weight loss ratio of the glass cloth after heat treatment after removing the attached components that are decomposed by heat at 380°C is the weight loss ratio derived from the glass components.

[0022] It was also confirmed that the weight reduction rate depends on the filament diameter of the glass yarn. The weight reduction rate varies depending on the glass filament diameter, and the smaller the filament diameter, the greater the weight reduction amount. On the other hand, the product of the weight reduction rate and the filament radius is an almost constant value regardless of the filament diameter. Therefore, in this embodiment, the weight reduction coefficient is standardized by the filament diameter.

[0023] If the weight reduction coefficient exceeds 0.45, the strength is likely to decrease if left as is. However, in this embodiment, the strength decrease can be suppressed by adjusting the Fe content described later, and a glass cloth having a lower dielectric constant can be obtained from the composition of the glass cloth. Furthermore, if the weight reduction coefficient is 0.90 or less, the effect of Fe in suppressing the strength decrease is effective, and a significant decrease in strength can be suppressed.

[0024] The weight loss ratio can be measured by the following procedure. First, the glass cloth is placed in a dryer at 105°C ± 5°C and dried for 60 minutes, then the glass cloth is transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth is measured to the nearest 0.1 mg (glass cloth weight a). Next, the glass cloth is heated at 380°C for 2 hours, then the glass cloth is transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth is measured to the nearest 0.1 mg (glass cloth weight b after heat treatment). The weight lost due to the heat treatment is then determined, and the weight loss ratio (%) is calculated using the following formula (2). Weight reduction rate (%) = (ab) / a×100 ···(2)

[0025] The weight loss ratio obtained as described above is preferably 0.05 to 0.7%, more preferably 0.1 to 0.5%, and even more preferably 0.12 to 0.4%. When the weight loss ratio is 0.05% or more, it is likely to cause a decrease in strength if left as is. However, in this embodiment, the decrease in strength can be suppressed by adjusting the Fe content described later, and more preferably, the F content, and also a glass cloth having a lower dielectric constant can be obtained from the relationship of the composition constituting the glass cloth. Furthermore, when the weight loss ratio is 0.7% or less, the effect of Fe in suppressing the decrease in strength is effectively acted on, and a significant decrease in strength can be suppressed.

[0026] Next, the average diameter of the glass filaments of the glass yarn constituting the glass cloth is measured in accordance with JIS R3420, and the average filament diameter is calculated as half of the filament diameter. In this embodiment, when simply referring to glass filaments, it means glass monofilaments. The average radius of the glass filaments used in calculating the weight reduction coefficient is the average radius before the heat treatment. The average radius of the glass filaments thus calculated is preferably 1.25 to 4.5 μm, more preferably 1.5 to 3.75 μm, and even more preferably 1.75 to 2.7 μm.

[0027] The glass cloth used in the above-mentioned method for measuring the weight loss rate can be appropriately pretreated. For example, the glass cloth unwound from the intermediate roll after desizing (heat cleaning) has no attached matter on the glass filaments, and can be used as is in the above-mentioned method for measuring the weight loss rate.

[0028] On the other hand, when determining the weight reduction ratio for glass cloth to which a surface treatment agent such as a silane coupling agent has been applied, the physically adsorbed surface treatment agent such as the silane coupling agent can be washed away in advance with a good solvent such as alcohol or acetone, and then the weight reduction coefficient can be determined by the above method.

[0029] The term "physically adsorbed silane coupling agent" refers to a silane coupling agent that is attached to the glass filament, but is not a silane coupling agent that is bonded to the glass filament by a chemical bond. In contrast, a silane coupling agent that is bonded to the glass filament by a chemical bond is called a "chemically adsorbed silane coupling agent."

[0030] In addition, when the glass cloth contains organic impurities (such as a starch-based sizing agent applied during the glass yarn manufacturing process, or combustion residues in the heat cleaning process of the sizing agent), the weight reduction coefficient can be determined by the above method after removing the organic impurities adhering to the glass cloth in advance by a cleaning removal operation using alcohol, acetone, or the like.

[0031] The above-mentioned washing is to remove physically adsorbed silane coupling agent and organic impurities, and is not to remove chemically adsorbed silane coupling agent.However, even if heated at 380°C for 2 hours, chemically adsorbed silane coupling agent does not decompose, and even if a part of it decomposes, it does not exceed the error range, so in the measurement of weight loss rate in this embodiment, it is not necessary to remove chemically adsorbed silane coupling agent by pretreatment.

[0032] From the viewpoint of simplifying the decision as to whether or not to perform pretreatment, the glass cloth may be uniformly washed in advance with a good solvent such as alcohols, acetone, etc. for the measurement of the weight loss ratio. This allows the weight loss ratio to be measured under the same conditions, even if the glass cloth is pulled out from the intermediate roll after desizing treatment (heat cleaning) or has physically adsorbed silane coupling agent or organic impurities attached thereto.

[0033] As another method, when determining the weight loss coefficient, the amount of the surface treatment agent and organic impurities before and after heating are quantified, and the weight loss caused by the surface treatment agent is subtracted from the weight loss obtained to determine the weight loss coefficient derived from the glass component. As a method for determining the weight loss caused by the surface treatment agent, a known method such as the method for quantifying the amount of a silane coupling agent described in Japanese Patent No. 6472082 may be used.

[0034] The weight loss coefficient can be adjusted by increasing or decreasing a relatively volatile component in the composition of the glass cloth, such as the B content, and from a similar viewpoint, it can also be adjusted by increasing or decreasing other components.

[0035] In addition, the weight reduction coefficient can also be adjusted by increasing or decreasing the frequency with which the glass surface is exposed to a high-temperature atmosphere, by adjusting the spatial filling rate of glass in the glass cloth (weaving density or thickness), adjusting the degree of unraveling of the monofilaments constituting the glass yarn bundle by fiber-opening processing or the like, adjusting the monofilament diameter of the glass yarn used, and so on. That is, the weight reduction coefficient is not determined only by the composition of the glass cloth.

[0036] (composition) The composition of the glass cloth of this embodiment will be described below. The composition of the glass cloth is synonymous with the composition of the glass yarn constituting the glass cloth. In the composition of the glass cloth of this embodiment, the Fe content is 0.001% by mass or more and 0.05% by mass or less, preferably 0.01% by mass or more and 0.04% by mass or less, and more preferably 0.01% by mass or more and 0.03% by mass or less, calculated as Fe2O3. By having an Fe content of 0.001% by mass or more, it is possible to suppress the decrease in strength of the glass cloth due to heat treatment. Furthermore, by having an Fe content of 0.05% by mass or less, the necessary strength is maintained even in the glass cloth which is prone to a weight reduction coefficient exceeding 0.45 and a decrease in strength. Furthermore, by having an Fe content of 0.05% by mass or less, it is possible to suppress the in-plane variation and lot-to-lot variation of the dielectric constant. The Fe content can be adjusted according to the amount of raw material used to prepare the glass filaments.

[0037] The Si content of the glass cloth is preferably 40 to 60 mass%, more preferably 45 to 55 mass%, further preferably 47 to 53 mass%, and 48 to 52 mass% in terms of SiO2. Si is a component that forms the skeleton structure of the glass yarn. By having a Si content of 40 mass% or more, not only the strength reduction due to heat treatment is suppressed, but also the strength of the glass yarn itself before heat treatment is improved, and the breakage of the glass cloth tends to be suppressed more in the manufacturing process of the glass cloth and the post-process such as the manufacturing of a prepreg using the glass cloth. In addition, by having a Si content of 40 mass% or more, the dielectric constant of the glass cloth tends to be lowered more. On the other hand, by having a Si content of 60 mass% or less, the viscosity at the time of melting is lowered more in the manufacturing process of the glass filament, and a glass fiber with a more homogeneous glass composition tends to be obtained. For this reason, it is difficult for the obtained glass filament to have a part that is easily permeated or a part that is difficult to remove bubbles, so that the glass filament is less likely to have a part that is locally weak in strength, and as a result, the glass cloth composed of the glass yarn obtained using this is less likely to break. The Si content can be adjusted according to the amount of raw material used to prepare the glass filaments.

[0038] The B content of the glass cloth is preferably 15 to 30 mass%, more preferably 17 to 28 mass%, further preferably 20 to 27 mass%, further more preferably 21 to 25 mass%, and further more preferably 21 to 24 mass%, calculated as B2O3. When the B content is 15 mass% or more, the dielectric constant tends to be lowered. When the B content is 30 mass% or less, the strength reduction can be suppressed, and the moisture absorption resistance is improved, and the insulation reliability tends to be improved. The B content can be adjusted according to the amount of raw material used in the production of the glass filaments. When the B content may vary during the production of the glass filaments, the amount of the raw material can be adjusted in advance in anticipation of the variation.

[0039] The F content of the glass cloth is preferably 0.001 to 0.1% by mass, more preferably 0.001 to 0.05% by mass, and further preferably 0.001 to 0.01% by mass. Here, the F content is a value obtained by converting it to F2. By making the F content 0.001% by mass or more, the decrease in strength of the glass cloth due to the heat treatment is more suppressed, and the dielectric constant tends to decrease more. In addition, F reduces the viscosity of the molten glass in the glass manufacturing process. Therefore, by making the F content within a predetermined range, when a metal component such as Fe is incorporated into the glass structure, it is possible to uniformly disperse without localization, and form a uniform glass. The effect of Fe tends to be fully exerted. By making the F content 0.1% by mass or less, it is possible to suppress the decrease in strength of the glass thread itself before the heat treatment due to the F content being too high. In addition, by making both the Fe content and the F content within the above-mentioned predetermined range, the effect of suppressing the decrease in strength due to the heat treatment tends to be further improved. The F content can be adjusted according to the amount of raw material used for producing the glass filament.

[0040] The decrease in strength due to an excessive F content is not particularly limited, but is believed to be due to the following: As the F content increases, the phase separation of the glass composition becomes stronger, making it more difficult to homogenize the glass components.

[0041] The glass cloth may have other compositions in addition to those described above. The other compositions are not particularly limited, but examples thereof include Al, Ca, Mg, P, Na, K, Ti, and Zn.

[0042] The Al content of the glass cloth is preferably 10 to 20 mass%, more preferably 12 to 18 mass%, and further preferably 14 to 17 mass%, calculated as Al2O3. When the Al content is within the above range, the electrical properties and strength tend to be further improved. The Al content can be adjusted according to the amount of raw material used to prepare the glass filaments.

[0043] The Ca content of the glass cloth is preferably 1.0 to 6.0 mass%, preferably 2.0 to 5.0 mass%, and more preferably 2.5 to 4.0 mass%. When the Ca content is 1.0 mass% or more, the viscosity at the time of melting is further reduced in the manufacturing process of the glass filaments, and glass fibers having a more homogeneous glass composition tend to be obtained. Also, when the Ca content is 6.0 mass% or less, the dielectric constant tends to be further improved. The Ca content can be adjusted according to the amount of raw material used in manufacturing the glass filaments.

[0044] The Mg content of the glass cloth is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, even more preferably 0.001 to 1.0 mass% or less, still more preferably 0.005 to 0.5 mass% or less, and even more preferably 0.005 to 0.3 mass% or less, calculated as MgO. A Mg content of 5.0 mass% or less is preferred because phase separation during glass filament production is suppressed, the glass composition becomes uniform, and there is a tendency for variation in dielectric properties to be reduced.

[0045] In addition, the moisture absorption resistance of the obtained glass filaments is improved by suppressing phase separation during the production of the glass filaments. As a result, the obtained printed wiring board is less susceptible to the effects of a high humidity environment, and the environmental dependency of the dielectric constant can be reduced. The Mg content can be adjusted according to the amount of raw material used to produce the glass filaments.

[0046] The P content of the glass cloth is preferably 1.0 to 7.0 mass%, more preferably 2.0 to 6.5 mass%, further preferably 3.0 to 6.0 mass%, and even more preferably 3.0 to 5.5 mass%, calculated as P2O5. When the P content is 1.0 mass% or more, the dielectric constant tends to be lowered. When the P content is 7.0 mass% or less, the glass cloth tends to be less likely to break when passing through a squeeze roll or nip roll in a wet state in a fiber opening process or a surface treatment process during glass cloth production. In addition, phase separation during glass filament production is suppressed, and the moisture absorption resistance of the obtained glass filament is further improved. As a result, the obtained printed wiring board is less susceptible to the influence of a high humidity environment, and the environmental dependency of the dielectric constant can be reduced. The P content can be adjusted according to the amount of raw material used in glass filament production.

[0047] The above contents can be measured by ICP atomic emission spectrometry. Specifically, the Si content and B content can be obtained by decomposing a weighed glass cloth sample with sodium hydroxide under pressure, dissolving it with dilute nitric acid, and filtering it. The insoluble matter is then melted with sodium carbonate, combined with the filtrate to a constant volume, and the obtained sample is measured by ICP atomic emission spectrometry.

[0048] The Fe content, Al content, Ca content, Ma content, and P content can be obtained by decomposing a weighed glass cloth sample by heating with perchloric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, dissolving by heating with dilute aqua regia, and filtering the sample. The filtrate is made to a constant volume. The insoluble portion is then decomposed by heating with sulfuric acid, nitric acid, hydrochloric acid, and hydrogen fluoride to a constant solution, and the obtained sample is measured by ICP atomic emission spectrometry. The ICP atomic emission spectrometry can be performed using a PS3520VDD II manufactured by Hitachi High-Tech Science Corporation.

[0049] The F content was measured by burning a weighed glass cloth sample in a tubular electric furnace, and then absorbing the generated gas into an absorbing solution. The solution was analyzed by ion chromatography to determine the amount of fluoride ions (F - ) can be measured to determine the amount of chlorine contained in the sample. The combustion device can be an automatic sample combustion device (AQF-2100S) manufactured by Mitsubishi Chemical Analytech, and the measurement device can be an ion chromatograph ICS-1500 manufactured by Thermo Fisher Scientific.

[0050] The elastic modulus of the glass cloth is preferably 50 to 70 GPa, more preferably 50 to 63 GPa, and further preferably 53 to 63 GPa. The lower the elastic modulus of the glass cloth, the more likely it is to break. Therefore, when the elastic modulus is 50 GPa or more, in the glass cloth manufacturing process such as the opening process and the surface treatment process, the glass cloth tends to be less likely to break when it passes through a squeeze roll, a nip roll, or the like in a wet state. Also, in the post-process such as the manufacture of a prepreg, when the glass cloth is passed through a slit for the purpose of controlling the amount of resin impregnated into the glass cloth, the glass cloth tends to be less likely to break. When the elastic modulus of the glass cloth is 70 GPa or less, the texture of the glass cloth becomes soft, and when the glass cloth passes through a narrow gap such as a squeeze roll or a nip roll, the glass cloth tends to be less likely to break. Also, when the elastic modulus of the glass cloth is 70 GPa or less, the dielectric constant tends to be relatively lower. The elastic modulus can be measured by the method described in the examples. Also, the elastic modulus can be adjusted by the composition of the glass yarn.

[0051] The dielectric constant of the glass cloth of this embodiment is preferably 5.0 or less, more preferably 4.7 or less, even more preferably 4.5 or less, and particularly preferably 4.0 or less, at a frequency of 1 GHz. The lower the dielectric constant of the glass cloth, the greater the effect of the Fe content, making the present invention particularly useful. In this embodiment, the dielectric constant refers to the dielectric constant at a frequency of 1 GHz, unless otherwise specified.

[0052] (composition) Glass yarn is obtained by bundling a plurality of glass filaments and twisting them as necessary, and glass cloth is obtained by weaving the above glass yarns as warp and weft. Glass yarns are classified into multifilament and glass filaments are classified into monofilament.

[0053] The average diameter of the glass filaments constituting the warp and weft is preferably 2.5 to 9 μm, more preferably 3.0 to 7.5 μm, and even more preferably 3.5 to 5.4 μm. When the average diameter of the glass filaments is within the above range, the processability of the obtained substrate tends to be improved when processed by a mechanical drill, a carbon dioxide gas laser, or a UV-YAG laser. Therefore, a thin and highly dense printed wiring board can be realized. In particular, when the average diameter is 5.4 μm or less, the surface area per unit volume increases, which tends to cause a decrease in strength due to heat treatment, so that the effect of suppressing the decrease in strength of this embodiment becomes more important. In addition, when the average diameter is 2.5 μm or more, the surface area is reduced, which suppresses the volatilization of the glass components, and in addition, in the glass cloth manufacturing process such as the fiber opening process and the surface treatment process, when the glass cloth passes through a squeeze roll, a nip roll, or the like in a wet state, breakage tends to be less likely to occur. Furthermore, in post-processes such as the production of prepregs, breakage tends to be less likely to occur when the glass cloth is passed through a slit for the purpose of controlling the amount of resin impregnated into the glass cloth.

[0054] The weft density of the warp and weft threads constituting the glass cloth is preferably 30 to 120 threads / 25 mm, more preferably 40 to 110 threads / 25 mm, and further preferably 50 to 100 threads / 25 mm.

[0055] The thickness of the glass cloth is preferably 8 to 100 μm, more preferably 10 to 50 μm, further preferably 12 to 35 μm, and particularly preferably 12 to 20 μm. When the thickness of the glass cloth is within the above range, a thin glass cloth with relatively high strength tends to be obtained. In particular, when the thickness is 8 μm or more, the proportion of glass filaments occupying the vicinity of the surface of the glass cloth decreases, so that the amount of volatilization of glass components tends to decrease. In addition, when the thickness is 100 μm or less, the proportion of glass filaments occupying the vicinity of the surface of the glass cloth increases, so that the strength is likely to decrease due to the increase in the amount of volatilization of glass components, and the effect of suppressing the decrease in strength of the present invention becomes more important. Note that the weight reduction coefficient depends on the diameter of the filaments constituting the glass cloth, and is therefore unlikely to depend on the thickness. This tendency is maintained at least within the above thickness range.

[0056] The fabric weight (weight) of the glass cloth is preferably 8 to 250 g / m 2 and more preferably 8 to 100 g / m 2 and more preferably 8 to 50 g / m 2 and particularly preferably 8 to 35 g / m 2 It is.

[0057] The weave structure of the glass cloth is not particularly limited, but examples thereof include plain weave, sash weave, satin weave, twill weave, etc. Among these, the plain weave structure is more preferable.

[0058] (Surface treatment) The glass cloth may be surface-treated with a surface treatment agent. The surface treatment agent is not particularly limited, but may be, for example, a silane coupling agent, and may be used in combination with water, an organic solvent, an acid, a dye, a pigment, a surfactant, or the like, as necessary.

[0059] The silane coupling agent is not particularly limited, but examples thereof include compounds represented by formula (1). X(R) 3-n SiY n (1) (In formula (1), X is an organic functional group having at least one of an amino group and an unsaturated double bond group, each Y is independently an alkoxy group, n is an integer of 1 to 3, and each R is independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group.)

[0060] X is preferably an organic functional group having at least three or more of amino groups and unsaturated double bond groups, and more preferably an organic functional group having at least four or more of amino groups and unsaturated double bond groups.

[0061] The alkoxy group may be in any form, but from the viewpoint of stabilizing the treatment of the glass cloth, an alkoxy group having 5 or less carbon atoms is preferred.

[0062] Specific examples of the silane coupling agent include N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropylmethyldimethoxysilane and its hydrochloride, N-β-(N-di(vinylbenzyl)aminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-di(vinylbenzyl)aminoethyl)-N-γ-(N-vinylbenzyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β Examples of known simple substances include -(N-benzylaminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-benzylaminoethyl)-γ-aminopropyltriisoethoxysilane and its hydrochloride, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltrimethoxysilane, methacryloxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and the like, or mixtures thereof.

[0063] The molecular weight of the silane coupling agent is preferably 100 to 600, more preferably 150 to 500, and further preferably 200 to 450. Among these, it is preferable to use two or more silane coupling agents having different molecular weights. By treating the surface of the glass yarn with two or more silane coupling agents having different molecular weights, the density of the surface treatment agent on the surface of the glass cloth increases, and the reactivity with the matrix resin tends to be further improved.

[0064] [Method of manufacturing glass cloth] The method for producing the glass cloth of the present embodiment is not particularly limited, but may include, for example, a method having a weaving step of weaving glass yarns to obtain a glass cloth, and an opening step of opening the glass yarns of the glass cloth. If necessary, the method may also have a desizing step of removing a sizing agent attached to the glass yarns of the glass cloth, and a surface treatment step with a silane coupling agent.

[0065] The weaving method is not particularly limited as long as it is a method of folding the weft and warp threads to obtain a predetermined weave structure. The opening method is not particularly limited, but examples of the opening method include a method of processing the fibers with spray water (high pressure water opening), a vibro washer, ultrasonic water, a mangle, etc. Furthermore, the desizing method is not particularly limited, but examples of the method include a method of removing the sizing agent by heating. The surface treatment method includes a method of contacting a surface treatment agent containing a silane coupling agent with a glass cloth and drying it. The contact of the surface treatment agent with the glass cloth includes a method of immersing the glass cloth in the surface treatment agent, and a method of applying the surface treatment agent to the glass cloth using a roll coater, a die coater, a gravure coater, etc. The drying method of the surface treatment agent is not particularly limited, but examples of the drying method include hot air drying and a drying method using electromagnetic waves.

[0066] [Prepreg] The prepreg of the present embodiment includes the above-mentioned glass cloth and a matrix resin composition impregnated into the glass cloth. The prepreg including the above-mentioned glass cloth is less likely to cause a decrease in strength, and the yield of the final product is high. In addition, since the prepreg has excellent dielectric properties and excellent moisture absorption resistance, it is possible to provide a printed wiring board that is less susceptible to the influence of the usage environment, particularly in a high humidity environment, and has a small change in dielectric constant.

[0067] The prepreg of the present embodiment can be produced by a conventional method, for example, by impregnating the glass cloth of the present embodiment with a varnish prepared by diluting a matrix resin such as an epoxy resin with an organic solvent, volatilizing the organic solvent in a drying furnace, and curing the thermosetting resin to a B-stage state (semi-cured state).

[0068] Examples of the matrix resin composition include, in addition to the above-mentioned epoxy resins, thermosetting resins such as bismaleimide resins, cyanate ester resins, unsaturated polyester resins, polyimide resins, BT resins, and functionalized polyphenylene ether resins; thermoplastic resins such as polyphenylene ether resins, polyetherimide resins, liquid crystal polymers (LCPs) of wholly aromatic polyesters, polybutadiene, and fluororesins; and mixed resins thereof. From the viewpoint of improving dielectric properties, heat resistance, solvent resistance, and press moldability, the matrix resin composition may be a resin obtained by modifying a thermoplastic resin with a thermosetting resin.

[0069] The matrix resin composition may also contain inorganic fillers such as silica and aluminum hydroxide; flame retardants such as bromine-based, phosphorus-based, and metal hydroxides; other silane coupling agents; heat stabilizers; antistatic agents; ultraviolet absorbers; pigments; colorants; lubricants, etc.

[0070] [Printed Wiring Board] The printed wiring board of this embodiment includes the above-mentioned glass cloth. The printed wiring board of this embodiment is less likely to cause a decrease in strength, and the final product has a high yield. In addition, since the printed wiring board of this embodiment has excellent dielectric properties and excellent moisture absorption resistance, it can also have the effect of being less susceptible to the influence of the usage environment, particularly in a high humidity environment, and thus has a small change in the dielectric constant. EXAMPLES

[0071] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0072] [Physical properties of glass cloth] The physical properties of the glass cloth, specifically, the thickness of the glass cloth, the diameter of the filaments constituting the warp and weft, the number of filaments, and the weaving density (weaving density) of the warp and weft were measured in accordance with JIS R3420.

[0073] [Weight reduction coefficient] The weight loss coefficient was measured by the following procedure. First, the glass cloth pulled out from the intermediate roll was placed in a dryer at 105°C ± 5°C and dried for 60 minutes, then the glass cloth was transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth was measured to the nearest 0.1 mg (weight of glass cloth a). Next, the glass cloth was heated at 380°C for 2 hours, then the glass cloth was transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth was measured to the nearest 0.1 mg (weight of glass cloth after heat treatment b). Then, the weight reduction due to the heat treatment was determined, and the weight reduction ratio (%) was calculated using the following formula (2). Weight reduction rate (%) = (ab) / a×100 ···(2)

[0074] Next, the diameter of the monofilament was measured according to JIS R3420, Method B, and half of that value was defined as the radius of the monofilament. Although JIS R3420, Method B, requires that the diameters of 25 randomly selected filament cross sections be measured, the diameters of all the monofilaments constituting the glass yarn (multifilament) were measured, and the filament diameter was calculated as the average value. The weight loss coefficient was calculated from the weight loss rate (%) and the average radius (μm) of the glass filaments according to the following formula (1). Weight reduction coefficient = weight reduction ratio (%) × average radius of glass filaments (μm) (1)

[0075] [Elastic modulus] The elastic modulus was measured by the pulse-echo overlap method using a glass bulk as a test piece.

[0076] [Strength reduction confirmation test] Using the glass cloth obtained in the examples and comparative examples, prepregs were produced under the following conditions, and the strength was evaluated to see if it was sufficient. The glass cloth was continuously drawn out and conveyed, and the glass cloth was immersed in varnish and passed through a slit to adjust the amount of varnish applied. The glass cloth was then dried in a drying oven at 120°C to obtain a prepreg. The varnish used contained 65 parts by mass of methacrylated polyphenylene ether, 35 parts by mass of triallyl isocyanurate, 10 parts by mass of hydrogenated styrene-based thermoplastic elastomer, 25 parts by mass of bromine-based flame retardant, 65 parts by mass of spherical silica, 1 part by mass of organic peroxide, and 210 parts by mass of toluene.

[0077] For each of the glass cloths obtained in the Examples and Comparative Examples, ten product rolls of 2000 m each were fabricated into prepregs by the above-mentioned method. Based on the fabrication results, the strength reduction was confirmed according to the following evaluation criteria. A: When the glass cloth does not break and prepreg can be produced using 10 rolls of glass cloth, it is judged to be a glass cloth with excellent productivity and handling properties. B: In the process of producing prepreg, one glass cloth roll breaks, but the remaining nine rolls are able to produce prepreg without breaking. It is determined that the glass cloth has sufficient strength for practical use. C: In the process of producing the prepreg, breakage occurred in 2 to 3 glass cloth rolls, but the remaining rolls were able to produce prepreg without breakage. It was determined that the glass cloth needed to be improved in strength. D: During the prepreg production process, breakage occurred in four or more glass cloth rolls.

[0078] [Evaluation of variation in dielectric tangent] From the prepregs prepared using the glass cloths obtained in the Examples and Comparative Examples, 100 test pieces for measuring electrical properties were randomly prepared, and the dielectric loss tangents were measured. Based on the measurement results, the variation in the dielectric loss tangent was evaluated according to the following evaluation criteria. A: None of the test pieces exhibited a dielectric tangent of 0.0028 or more. B: There was one test piece that exhibited a dielectric tangent of 0.0028 or more. C: There were 2 to 3 test pieces that showed a dielectric tangent of 0.0028 or more. D: There were four or more test pieces that exhibited a dielectric tangent of 0.0028 or more.

[0079] The prepreg was prepared in the same manner as the strength reduction method. The test piece for measuring electrical properties was prepared in the following manner. A predetermined number of prepregs were stacked so that the thickness of the laminate was about 1 mm, and copper foil (GTS-MP foil, 18 μm thick, manufactured by Furukawa Electric Co., Ltd.) was placed on both sides of the stacked prepregs, and the laminate was obtained by vacuum pressing. Next, the copper foil was removed from the copper-clad laminate by etching to obtain a laminate.

[0080] A test piece having a length of about 50 mm and a width of about 1.5 mm was cut out from the obtained laminate so that the warp threads of the glass cloth were the long sides, and used as a test piece for electrical property testing.

[0081] The dielectric tangent was measured by the following method. The test piece for measuring electrical properties was placed in an oven at 105°C±2°C and dried for 2 hours, then left to stand in a thermostatic chamber at 23±2°C and relative humidity 50±5% for 96 hours, after which the dielectric constant at 10 GHz was measured. The measuring equipment used was a network analyzer (N5230A, manufactured by Agilent Technologies) and a cavity resonator (Cavity Resornator CP series) manufactured by Kanto Electronics Application Development Co., Ltd., and the measurement itself was carried out in an environment of 23±2°C and relative humidity 50±5%.

[0082] [Glass Cloth Composition] The composition of the glass cloth was measured by ICP atomic emission spectrometry. Specifically, the Si content and B content were measured by pressure-decomposing a weighed glass cloth sample with sodium hydroxide, dissolving it in dilute nitric acid, and filtering it. The insoluble matter was dissolved in sodium carbonate, combined with the filtrate, and the volume was determined. The obtained sample was measured by ICP atomic emission spectrometry.

[0083] The Fe, Al, Ca, Ma, and P contents were measured by decomposing the weighed glass cloth sample with perchloric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, then dissolving it by heating with dilute aqua regia and filtering it. The filtrate was made to a constant volume. The insoluble matter was decomposed with sulfuric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, and dissolved to a constant volume. The obtained sample was measured by ICP atomic emission spectrometry. The ICP atomic emission spectrometry was performed using a PS3520VDD II manufactured by Hitachi High-Tech Science Corporation.

[0084] Furthermore, the F content was measured by burning a weighed glass cloth sample in a tubular electric furnace, and then absorbing the generated gas into an absorbing solution. The solution was analyzed by ion chromatography to determine the amount of fluoride ions (F - The content in the sample was calculated by measuring the amount of benzene in the sample. The combustion device used was an automatic sample combustion device (AQF-2100S) manufactured by Mitsubishi Chemical Analytech, and the measurement device was an ion chromatograph ICS-1500 manufactured by Thermo Fisher Scientific.

[0085] Example 1 Low dielectric glass yarn consisting of 50 filaments with an average filament diameter of 4.0 μm was woven using an air jet loom to obtain glass cloth with a warp and weft density of 94 / 25 mm and a thickness of 14 μm. Next, a desizing treatment was performed by heating to obtain an intermediate glass cloth roll with a width of 1280 mm and a length of 2000 m. Next, a fiber opening process was performed using a high-pressure water spray, and a surface treatment was performed using a silane coupling agent to produce a glass cloth roll. The composition of the obtained glass cloth was as shown in Table 1.

[0086] [Examples 2 to 5] Except for the different composition of the glass yarn, a roll of glass cloth was obtained in the same manner as in Example 1. The composition of the obtained glass cloth was as shown in Table 1.

[0087] Example 6 A roll of glass cloth was obtained in the same manner as in Example 1, except that glass yarn having the same composition as in Example 2 was used, and the degree of fiber spreading was reduced by shortening the time in the fiber spreading step and weakening the spray pressure. The composition of the obtained glass cloth was as shown in Table 1.

[0088] [Comparative Examples 1 to 6] Except for the different composition of the glass yarn, a roll of glass cloth was obtained in the same manner as in Example 1. The composition of the obtained glass cloth was as shown in Table 2.

[0089] Comparative Example 7 A roll of glass cloth was obtained in the same manner as in Example 2, except that glass yarn having the same composition as in Example 2 was used, and the degree of fiber spreading was increased by lengthening the time in the fiber spreading step and increasing the spray pressure. The composition of the obtained glass cloth was as shown in Table 2.

[0090] Example 7 A roll of glass cloth was obtained in the same manner as in Example 1, except that low dielectric glass yarn having an average filament diameter of 5.0 μm and 200 filaments was woven by an air jet loom to produce glass cloth having a warp and weft pick density of 69 / 25 mm and a thickness of 30 μm. The composition of the obtained glass cloth was as shown in Table 1.

[0091] Example 8 A roll of glass cloth was obtained in the same manner as in Example 7, except that the packing density of the warp and weft was set to 55 yarns / 25 mm, respectively. The composition of the obtained glass cloth was as shown in Table 1.

[0092] Comparative Example 8 A roll of glass cloth was obtained in the same manner as in Example 8, except that the degree of fiber opening was increased by lengthening the time in the fiber opening step and increasing the spray pressure. The composition of the obtained glass cloth was as shown in Table 2.

[0093] Example 9 A roll of glass cloth was obtained in the same manner as in Example 1, except that low dielectric glass yarn having an average filament diameter of 7.0 μm and 200 filaments was woven by an air jet loom to produce glass cloth having a warp and weft placement density of 60 / 25 mm and a thickness of 92 μm. The composition of the obtained glass cloth was as shown in Table 1.

[0094] [Reference example 1] Except for using glass yarn having an E-glass composition, a roll of glass cloth was obtained in the same manner as in Example 1. The composition of the obtained glass cloth was as shown in Table 2.

[0095] [Table 1]

[0096] [Table 2]

[0097] The glass cloth of Examples 1 to 3 and 6 to 9 could be stably produced without breakage of the glass cloth in all 10 rolls (Evaluation A). In addition, the glass cloth of Examples 4 and 5 broke in only one roll, but the remaining nine rolls could be stably produced (Evaluation B). In addition, the glass cloth of Reference Example 1 did not break or show any variation in dielectric loss tangent, but had poor electrical properties, and it is clear that breakage and variation in dielectric loss tangent are problems that are particularly likely to occur in low dielectric glass cloth.

[0098] On the other hand, the glass cloths of Comparative Examples 1, 2, and 5 to 8 broke on two or three rolls (Grade C). This is insufficient for stably supplying printed wiring boards using low dielectric glass, and improvement is required. Furthermore, the glass cloths of Comparative Examples 3 and 4 broke on four consecutive rolls from the start of coating, so the coating test had to be stopped (Grade D).

[0099] The dielectric loss tangents of the printed wiring boards evaluated using the glass cloths of Examples 1, 2, and 4 to 9 were all less than 0.0028, and the glass cloths were very reliable (evaluated as A). The glass cloth of Example 3 had only one sample with a dielectric loss tangent of 0.0028 or more, and was a relatively reliable glass cloth (evaluated as B). On the other hand, the glass cloths of Comparative Examples 3 and 4 had four or more samples with a dielectric loss tangent of 0.0028 or more, and were poorly reliable glass cloths (evaluated as D).

[0100] In addition, all of the examples and comparative examples had a dielectric constant of about 3.0 and were low dielectric glass cloths, but Reference Example 1 had a dielectric constant of about 5.1 and could not be considered a low dielectric glass cloth. [Industrial Applicability]

[0101] INDUSTRIAL APPLICABILITY The present invention has industrial applicability as a low dielectric glass cloth used for prepregs and the like.

Claims

1. A glass cloth constructed by using glass yarns made of a plurality of glass filaments as warp yarns and weft yarns, In the following formula (1), a weight reduction coefficient calculated as the product of the weight reduction rate derived from the glass component in a heat treatment at 380° C. for 2 hours and the average radius of the glass filaments is more than 0.45 and 0.90 or less, Weight reduction coefficient=weight reduction ratio (%)×average radius of the glass filaments (μm) (1) The Fe content of the glass cloth is Fe 2 O 3 In terms of weight percent, it is 0.001% by weight or more and 0.05% by weight or less. Glass cloth.

2. The glass cloth, The F content is 0.001 to 0.1 mass%. The glass cloth according to claim 1.

3. The glass cloth, The Si content is SiO 2 In terms of mass conversion, it is 40 to 60 mass %, B content is B 2 O 3 In terms of mass conversion, it is 15 to 30 mass%. The glass cloth according to claim 1 or 2.

4. The elastic modulus of the glass cloth is 50 to 70 GPa. The glass cloth according to any one of claims 1 to 3.

5. The elastic modulus of the glass cloth is 50 to 63 GPa. The glass cloth according to claim 4.

6. The average diameter of the glass filaments constituting the warp and weft yarns is independently 3.5 to 5.4 μm. The glass cloth according to any one of claims 1 to 5.

7. having a dielectric constant of 5.0 or less at a frequency of 1 GHz; The glass cloth according to any one of claims 1 to 6.

8. The glass cloth according to any one of claims 1 to 7, and a matrix resin impregnated in the glass cloth. Prepreg.

9. The glass cloth according to any one of claims 1 to 7 is provided. Printed wiring board.

Citation Information

Patent Citations

  • Low dielectric constant glass fiber

    JP1999292567A